«Ta'arof» is the main aspect of the Iranian mentality - М.М. Абишева; А.М. Курбанбаева (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
The article considers the peculiarities of politeness in the Iranian speech culture. It also reveals the universal and the particular, describes the factors and reasons of cultural specificity. The purpose of this article is to study these features of the Iranian national character. To achieve this goal, the author reviewed the main features of the Iranian national behavior and the factors of their formation. Results of the survey to identify the general views of Iranian students on the concept of „politeness”. The hypotheses of Iranian and foreign researchers about social relations in Iranian society are presented. The article also presents scientific hypotheses about the origin of «ta'arof» and examples from the Hadith which affect a variety of religious and legal aspects of the life of the Muslim community.